SISTEM PAKAR MENDIAGNOSA KERUSAKAN KOMPUTER DENGAN METODE FORWARD CHAINING BERBASIS WEB - Debora Margaretta Br Simanjuntak; Pangaribuan, Hotma (Computer Science and Industrial Engineering, 2022)
At present PC experts need quite a while to analyze the harm that happens to a PC, even a few professionals frequently defer their work just to deliver a "answer" of the PC harm. With the improvement of master frameworks, it can likewise be utilized to give suitable and quick arrangements, for instance in deciding the kind of harm to the computer.The answer for this issue is to plan programming utilizing the forward binding strategy where the technique is a following/thinking process while utilizing a derivation motor and can be portrayed legitimately as an application. Forward tying is a genuinely well known execution procedure for master frameworks. This technique is very appropriate for use by master frameworks that analyze something unsure by doing following/thinking to decide the aftereffects of the evaluation. The advantages got from a specialist framework that can make a fast, exact and precise finding of the side effects of harm that frequently happen and are supposed to have the option to help professionals in giving arrangements and legitimate treatment of harm that happens on the PC.